Deconstruction of leadership accountability of neoliberalist universities based on Ki Hajar dewantara's trilogy leadership - Rahman, Arief; Djamhuri, Ali (Accounting Department,, 2024)
Purpose: This study aims to deconstruct the concept of university leadership accountability, which is often influenced by neoliberal values, by applying Ki Hajar Dewantara's philosophical framework. Method: The study employs a deconstructive approach, utilizing three operating modes: description, analysis, and transformation. This involves describing the current reality of neoliberal leadership accountability, analyzing its explicit and implicit meanings, and finally, transforming the concept to align with the values espoused by Ki Hajar Dewantara. Findings: The deconstruction process reveals a concept of leadership accountability that emphasizes moral, spiritual, and sincere compassion. This approach reflects the spirit of Ki Hajar Dewantara's